Penerapan media ular tangga dalam meningkatkan efektivitas belajar terhadap mahasiswa - Ardiansyah, Muhammad Rifan (Maliki Interdisciplinary Journal, 2025)
This study aims to determine how well the utilization of learning media based on snakes and ladders games. The subjects of the study were fifth semester students of the Islamic Religious Education study program. This study uses a qualitative method with a descriptive approach and a literature review as its support. The research data was taken from a sample of fifth semester students of the study program and several article references from Google Scholar. The results show that the snakes and ladders game media is effective in improving student understanding while supporting learning efficiency. This interactive learning method has also been proven to be able to increase learning motivation, active participation, and student understanding of the Fiqih